What are Qualitative Research Ethics? - Wiles, Rose (Bloomsbury Academic, 2012)
There has been an increasing interest in research ethics over the last decade or so in the light of the increasing ethical regulation of social research. Enhancing 'ethical literacy' means encouraging researchers to understand and engage with ethical issues as they emerge throughout the process of research. This book offers a short, succinct and accessible overview of the field. Wiles clearly identifies the key issues that researchers are likely to face, and the everyday ethical dilemmas that researchers encounter in a range of different contexts. The book covers a broad range of methods with clear guidance for researchers on how to identify an approach that fits with their moral and intellectual framework. It explores ethical issues relating to 'traditional' research methods as well as those relating to new and emerging methods and approaches, particularly visual and online methods. Illustrated throughout with real-world examples, this book also includes an annotated bibliography of key texts and other helpful resources. I‰What are Qualitative Research Ethics? /I‰will be a vital resource for social science researchers across a broad range of disciplines.